Merosin-deficient congenital muscular dystrophy type 1a: detection of LAMA2 variants in Vietnamese patients - Tran, Van Khanh; Nguyen, Ngoc-Lan; Tran, Lan Ngoc Thi; Le, Phuong Thi; Tran, Anh Hai; Pham, Tuan L. A.; Lien, Nguyen Thi Kim; Xuan, Nguyen Thi; Thanh, Le Tat; Ta, Thanh Van; Tran, Thinh Huy; Nguyen, Huy-Hoang (Frontiers in Genetics, 2023)
Background: Merosin-deficient congenital muscular dystrophy type 1A (MDC1A), also known as laminin-α2 chain-deficient congenital muscular dystrophy (LAMA2-MD), is an autosomal recessive disease caused by biallelic variants in the LAMA2 gene. In MDC1A, laminin- α2 chain expression is absent or significantly reduced, leading to some early-onset clinical symptoms including severe hypotonia, muscle weakness, skeletal deformity, non-ambulation, and respiratory insufficiency. Methods: Six patients from five unrelated Vietnamese families presenting with congenital muscular dystrophy were investigated. Targeted sequencing was performed in the five probands. Sanger sequencing was carried out in their families. Multiplex ligation-dependent probe amplification was performed in one family to examine an exon deletion. Results: Seven variants of the LAMA2 (MN_000426) gene were identified and classified as pathogenic/likely pathogenic variants using American College of Medical Genetics and Genomics criteria. Two of these variants were not reported in the literature, including c.7156-5_7157delinsT and c.8974_8975insTGAT. Sanger sequencing indicated their parents as carriers. The mothers of family 4 and family 5 were pregnant and a prenatal testing was performed. The results showed that the fetus of the family 4 only carries c.4717+5G>A in the heterozygous form, while the fetus of the family 5 carries compound heterozygous variants, including a deletion of exon 3 and c.4644C>A. Conclusion: Our findings not only identified the underlying genetic etiology for the patients, but also provided genetic counseling for the parents whenever they have an offspring.